2015
DOI: 10.2113/gsjfr.45.4.390
|View full text |Cite
|
Sign up to set email alerts
|

The Devil Lies in Details: New Insights Into the Behavioural Ecology of Intertidal Foraminifera

Abstract: The motion behaviour of three species of intertidal foraminifera, Ammonia tepida, Cribroelphidium excavatum and Haynesina germanica, was investigated continuously in the laboratory. We first infer the presence of geotactic and phototactic responses. Significant geotactic responses were observed for all three species; A. tepida was found to be negatively geotactic while C. excavatum and H. germanica showed positive geotaxis. In contrast, no response to light was ever observed. The detailed nature of motility, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 63 publications
(95 reference statements)
3
22
1
Order By: Relevance
“…Specifically, locomotion speed was nearly 2-fold lower than those reported previously on the same species (here ~2 mm h -1 vs. ~4 mm h -1 in Seuront and Bouchet, 2015) probably due to the lower experimental temperature (12°C here vs. 22°C in Seuront and Bouchet, 2015) since decreasing temperature is known to reduce foraminiferal activity (Bradshaw, 1961). Our results nevertheless clearly indicated that PP leachates did not affect foraminiferal behavior (Figure 2A, B).…”
Section: Discussioncontrasting
confidence: 64%
“…Specifically, locomotion speed was nearly 2-fold lower than those reported previously on the same species (here ~2 mm h -1 vs. ~4 mm h -1 in Seuront and Bouchet, 2015) probably due to the lower experimental temperature (12°C here vs. 22°C in Seuront and Bouchet, 2015) since decreasing temperature is known to reduce foraminiferal activity (Bradshaw, 1961). Our results nevertheless clearly indicated that PP leachates did not affect foraminiferal behavior (Figure 2A, B).…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, as H . germanica behaviour does not seem to be light driven [ 39 ] their photo-regulation capacity is likely to depend mainly on their kleptoplast physiological capabilities as for other kleptoplastic organisms [ 23 , 41 , 46 ]. We addressed this gap in current knowledge by investigating how H .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if H . germanica is not sensitive to light [ 39 ] then we can hypothesise that the xanthophyll cycle might be an important short-term photoprotective mechanism for the diatom kleptoplasts incorporated in the foraminifera cytosol. This was supported by our experiments, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murray (2006) considered Ammonia species as strictly infaunal which is not the case in this study; as Ammonia beccarii seems to be an epifaunal species for the three biotopes (Seuront & Bouchet, 2015).…”
Section: Discussionmentioning
confidence: 85%